Las mejores obras de principios de siglo = The very best works at the turn of the Century. - Cecilia, Fernando Marquez, ....-; Levene, Richard C., 1957- (El Escorial : El Croquis, 2011)
A selection of the most prominent works of architecture selected by El Croquis with an introduction by Juan Antonio Cortés and an essay by William Curtis. Among the works are the Sendai Mediatheque by Toyo Ito, the Yokohama International Port Terminal by Foreign Office Architects, the Netherlands Embassy in Berlin by OMA-Rem Koolhaas, the Braga Municipal Stadium by Eduardo Souto de Moura, the Prada Aoyama Epicenter by Herzog & De Meuron, the Scottish Parliament building by EMBT, the Monastery of Our Lady of Novy Dvur by John Pawson, the Nelson Atkins Museum of Art expansion by Steven Holl, the Neues Museum by David Chipperfield, the Toledo Glass Pavilion by Sanaa-Sejima & Nishizawa and others.
Juan Antonio Cortes: Strong Forms; William Curtis: Ideas of Architecture and Architectural Ideas.
Toyo Ito: Sendai Mediatheque, Sendai, Japan.
Foreign Office Architects: Yokohama International Port Terminal, Japan.
OMA/Rem Koolhaas: Netherlands Embassy in Berlin.
Eduardo Souto de Moura: Braga Municipal Stadium.
Herzog & De Meuron: Prada Aoyama EpicenterTokyo, Japan.
Herzog & De Meuron: IKMZ BTU Cottbus, Tyskland.
Keywords: Moderne arkitektur; Architectuur -- 21ste eeuw; Architectuur